Evaluating microbiological safety and associated handling practices of butchery-sold meat in Nairobi, Kenya - Koech, Patricia Cherotich; Ogutu, Winnie Aketch; Ochieng, Linnet; Grace, Delia; Gitao, George; Bebora, Lilly; Korir, Max; Mutua, Florence; Moodley, Arshnee (Frontiers in Sustainable Food Systems, 2024)
Introduction Approximately 70% of diarrheal cases in Kenya are attributed to ingestion of contaminated food and water and costs an estimated 1 billion USD due to morbidity and cost of treatment. This study aimed to assess the levels of microbiological contamination of meat sold in selected butcheries in Nairobi and the handling practices of butcher shop attendants. Methods A cross-sectional study design was used during which 200 meat samples were collected, and meat handling practices were observed. Total coliforms and Escherichia coli were enumerated using 3M™ Petrifilm® count plates. Additionally, quantification of tetracycline- and cefotaxime-resistant Enterobacteriaceae was done on agar plates containing the respective antibiotics. Bacterial species were confirmed by Matrix-Assisted Laser Desorption/Ionization-Time of Flight mass spectrometry. Results and discussion Seventy two percent and 84% of the samples had E. coli and total coliforms respectively above the acceptable regulatory limits (i.e. E. coli >100 CFU/g, Total coliforms >361 CFU/g,) respectively as per the Kenya Bureau of Standards South African microbiological standards the European Union. Enterobacteriaceae resistant to tetracycline and cefotaxime were detected in 35% and 9.5% of the samples respectively. Eighty-five percent of the butcher shop attendants neither washed their hands before nor after handling the meat, 91% handled money while selling meat concurrently, and 99% did not wear gloves while handling meat. These poor meat handling practices coupled with the presence of microbial loads above the regulatory acceptable limits imply an increased risk of foodborne illness to consumers. Therefore, there is an urgent need for education of butcher shop attendants on appropriate handling of meat, highlighting the importance of good hygienic practices and their relationship to food safety, and provision of incentives for behavior change. This study is important and serves to inform policymakers in the identification of key control points for designing meat safety intervention(s).